2019
DOI: 10.1038/s41598-019-49339-y
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from Adipose-Derived Stem Cells (ADSCs) Overexpressing miR-21 Promote Vascularization of Endothelial Cells

Abstract: In the past few years, exosomes released from adipose-derived stem cells (abbreviated as ADSCs) have shown promises to provide therapeutic benefits in the fields of regenerative medicine. miRNAs, existing in exosomes, are endogenous, small noncoding RNAs that play important roles in a variety of cellular functions and tumor development. Emerging evidences have indicated that miR-21 is one of the important miRNAs associated with tumor angiogenesis. In this study, we identified the role of exosomes from ADSCs ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 48 publications
1
93
0
1
Order By: Relevance
“…Others have confirmed the stimulation of ADSCs proliferation and keratinocytes chemoattraction via HIF-1α and VEGF, which are involved in angiogenesis and are facilitated by MMP [114,115]. Recently, SDF-1 has been released, together with HIF-1α in exosomes of ADSCs overexpressing miR-21, and potentially promotes angiogenesis [116]. Similar results were reported recently when using multiple injections of autologous ADSCs to burn wounds in the animal model, where angiogenesis was found to have an enhanced association with the increase in VEGF expression [78].…”
Section: Angiogenesismentioning
confidence: 90%
“…Others have confirmed the stimulation of ADSCs proliferation and keratinocytes chemoattraction via HIF-1α and VEGF, which are involved in angiogenesis and are facilitated by MMP [114,115]. Recently, SDF-1 has been released, together with HIF-1α in exosomes of ADSCs overexpressing miR-21, and potentially promotes angiogenesis [116]. Similar results were reported recently when using multiple injections of autologous ADSCs to burn wounds in the animal model, where angiogenesis was found to have an enhanced association with the increase in VEGF expression [78].…”
Section: Angiogenesismentioning
confidence: 90%
“…Yi et al (2019) reported that exosomes from osteocalcin-overexpressed EPCs showed a beneficial effect by stimulating the endothelial OCN-GPRC6A signaling. An et al (2019) reported that exosomes from ADSCs overexpressing miR-21 promote vascularization. Despite these beneficial effects, it is worthy to note that these genetic modifications of donor cells may also cause unwanted changes in exosomes.…”
Section: Anti-fibrotic Effects Of Ipsc-exosomesmentioning
confidence: 99%
“…Microvesicle transport of miR-31 from ASC to endothelial cells has been shown to enhance angiogenesis [33]. It has also been recently shown that exosomes derived from murine ASC over-expressing miR-21 led to enhanced vascularisation of an endothelial cell line in vitro [34]. However, further studies are required to accurately determine the microRNA profile that is present in microvesicles derived from ex vivo ASC.…”
Section: Discussionmentioning
confidence: 99%